Time to Optimize Supplementation: Modifying Factors Influencing the Individual Responses to Extracellular Buffering Agents - Heibel, André B.; Perim, Pedro H. L.; Oliveira, Luana F.; McNaughton, Lars R.; Saunders, Bryan (Frontiers in Nutrition, 2018)
Blood alkalosis, as indicated by an increased blood bicarbonate concentration and pH, has been shown to be beneficial for exercise performance. Sodium bicarbonate, sodium citrate and sodium or calcium lactate, can all result in increased circulating bicarbonate and have all independently been shown to improve exercise capacity and performance under various circumstances. Although there is considerable evidence demonstrating the efficacy of these supplements in several sports-specific situations, it is commonly acknowledged that their efficacy is equivocal, due to contrasting evidence. Herein, we discuss the physiological and environmental factors that may modify the effectiveness of these supplements including, i) absolute changes in circulating bicarbonate; ii) supplement timing, iii) the exercise task performed, iv) monocarboxylate transporter activity; v) training status, and vi) associated side-effects. The aim of this narrative review is to highlight the factors which may modify the response to these supplements, so that individuals can use this information attempt to optimise supplementation and allow the greatest possibility of an ergogenic effect.